Assessing the Climate Impact of Building Demolition: A study of module C (end-of-life) impacts from two Swedish Demolition Projects - Fredriksson (My University, 2026)
As the construction sector aims to reduce its climate impact, including all lifecycle stages in assessments becomes increasingly important. In Sweden, Boverket proposes to extend the current climate declaration regulation to include modules B – use and C- end-of-life by 2027. However, there is currently a lack of research around climate impacts of module C. This thesis assesses the scale, drivers and distribution of climate impacts associated with building demolition, through calculating the climate impacts of module C – end-of-life for two demolished buildings in Sweden. Project specific data on the two case studies was collected in terms of demolished quantities, waste management strategies and transported distanced. By applying generic climate data, the climate impact was calculated for sub-modules C1-C4 as per EN 15978. The total climate impact of module C was estimated to 25-29 kg CO2e/m2 GFA for project A and 20 – 25 kg CO2e/m2 GFA for project B, indicating that the climate impact of end-of-life processes is small but not negligible. Sub-modules C3 C4 - waste processing and disposal – were the largest contributors, while C2 – transport of waste – was the smallest but most actionable in terms of mitigation. The results indicate a dependency on material as concrete was identified as the main driver of climate impacts across all sub-modules. Additionally, the results are sensitive to the distance of transport, which can be affected by the choice of waste management strategy. The study is subject to several uncertainties due to lack of data and identifies the largest data gap regarding required on-site machinery for calculation of sub-module C1- demolition and deconstruction. The results demonstrate that, regardless of uncertainties, it is possible to estimate the climate impact of module C post demolition. However, the appropriate allocation of these impacts remains an open question, particularly in cases where demolition is undertaken as part of a broader building replacement project.
Keywords: Life cycle assessment (LCA); end-of-life (EoL); demolition; module C; climate impact